Connecticut needlework : women, art, and family, 1740-1840 - Schoelwer, Susan Prendergast (Connecticut Historical Society ; Distributed by Wesleyan University Press, 2010)
"From barefoot apostles to quilted mermaids, the needle-work in this book surprises and enlightens anyone who thinks the history of early American women has all been written."--Laurel Thatcher Ulrich, autor of The Age of Homespun Objects and Stories in the Creation of an American Myth